2002
DOI: 10.1182/blood.v100.6.2071
|View full text |Cite
|
Sign up to set email alerts
|

Acute thrombocytopenia after treatment with tirofiban or eptifibatide is associated with antibodies specific for ligand-occupied GPIIb/IIIa

Abstract: Acute thrombocytopenia is a recognized complication of treatment with GPIIb/IIIa inhibitors whose cause is not yet known. We studied 9 patients who developed severe thrombocytopenia (platelets less than 25 × 109/L) within several hours of treatment with the GPIIb/IIIa inhibitors tirofiban (4 patients) and eptifibatide (5 patients). In each patient, acute-phase serum contained a high titer (range, 1:80-1:20 000) IgG antibody that reacted with the glycoprotein IIb/IIIa complex only in the presence of the drug us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
115
0
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(119 citation statements)
references
References 39 publications
1
115
0
3
Order By: Relevance
“…7 Ligand-Mimetic Agents A case series of nine patients treated with ligand-mimetic agents (four received tirofiban, five received eptifibatide) demonstrated that the thrombocytopenia was the result of antibodymediated platelet destruction. 8 The serum of each patient contained a high titer of immunoglobulin G antibody that reacted with the glycoprotein IIb-IIIa complex in the presence of the study drug. Antibodies cross-reacted with other glycoprotein IIb-IIIa inhibitors in only one of the nine patients; no antibodies cross-reacted with abciximab.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7 Ligand-Mimetic Agents A case series of nine patients treated with ligand-mimetic agents (four received tirofiban, five received eptifibatide) demonstrated that the thrombocytopenia was the result of antibodymediated platelet destruction. 8 The serum of each patient contained a high titer of immunoglobulin G antibody that reacted with the glycoprotein IIb-IIIa complex in the presence of the study drug. Antibodies cross-reacted with other glycoprotein IIb-IIIa inhibitors in only one of the nine patients; no antibodies cross-reacted with abciximab.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, abciximab in vitro has inhibited the antibody reaction that causes thrombocytopenia associated with the ligandmimetic agents. 8 The proposed mechanism for this lack of cross-reactivity is the steric hindrance the molecule provides after binding to the glycoprotein IIb-IIIa receptor.…”
Section: Cross-reactivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Because circulating antiidiotypic antibodies would compete with platelet integrin α ΙΙb β 3 for RAD antibody binding rather than bind to the platelet surface through the RAD antibodies, it is a reasonable assumption that they would not cause severe thrombocytopenia. An interesting recent finding was that human antibodies that selectively recognized integrin α ΙΙb β 3 when complexed with tirofiban and eptifibatide were found in the very limited number of patients who developed severe thrombocytopenia after being treated with the small molecule drugs (41). In this context, the possibility remains that RAD antibodies could cause thrombocytopenia by inducing the display of immunogenic epitopes on integrin α ΙΙb β 3 as their binding mode mimics the small molecule drugs.…”
Section: Discussionmentioning
confidence: 99%
“…The only trial that directly compared abciximab to tirofiban showed a statistically significant increased risk of thrombocytopenia in the abciximab arm compared with the tirofiban arm [5]. Several reports of acute (within 24 hr after the bolus) and severe thrombocytopenia have been published for abciximab [6,7]; there are very few for eptifibatide [8][9][10][11], and only four cases of thrombocytopenia associated with tirofiban treatment have been reported with scarce clinical details [8]. We report on three cases of acute thrombocytopenia most likely attributable to tirofiban (Aggrastat TM ) treatment and comment on the practical management of the persistent thrombotic risk with particular emphasis on the importance of ruling out heparininduced thrombocytopenia.…”
Section: Introductionmentioning
confidence: 99%